The potential of Trichoderma sp. as antibacterial and immunostimulant on white shrimp (Litopenaeus vannamei) - Pebrianto, Catur A.; Sukenda, .; Widanarni, . (Indonesian Society of Scientific Aquaculture (ISSA), 2010)
The objective of this research was to study antibacterial and immunostimulatory effects of Trichoderma sp. extract on white shrimp, Litopenaeus vannamei. First experiment was conducted to evaluate inhibitory effect of Trichoderma sp. againts Vibrio harveyi, a pathogenic bacteria causing vibriosis disease on shrimp. Second experiment was conducted to evaluate immunostimulatory effect of Trichoderma sp. on shrimp immunity as well as protective effect against V. harveyi. A group of shrimp was injected with a minimum inhibitory concentration obtained at first experiment, and a week after, shrimps was challenged with V. harveyi (prophylactic). Another group was previously challenged with V. harveyi, and subsequently injected with Trichoderma sp. two fold of Minimum Inhibitory Concentration (MIC) a day after (therapeutic). Positive control, that was received only V. harveyi, and negative controls, that was received neither Trichoderma sp. nor V. harveyi were included in this experiment. Results of first experiment showed that a concentration of 600 ppm was a MIC of Trichoderma sp. to inhibit V. harveyi. While in the second experiment, the groups receiving Trichoderma sp., either prophylactic or therapeutic, showed protective effect against V. harveyi significantly higher than positive control and lower compared with negative control. Total haemocyte count (THC), differential haemocyte count (DHC), phagocytic index and phenoloxydase activity were different among the groups of prophylactic treatment or therapeutic treatment compared to control positive and negative treatments. In conclusion, Trichoderma sp. could be used in prophylactic and therapeutic treatments to combat infection of V. harveyi on L. vannamei. Key words: Trichoderma sp., V. harveyi, immunostimulant ABSTRAK Penelitian ini bertujuan untuk mempelajari pengaruh antibakterial dan immunostimulasi ekstrak Trichoderma sp. terhadap udang putih, Litopenaeus vannamei. Percobaan pertama dilakukan untuk mengevaluasi pengaruh penghambatan Trichoderma sp. terhadap Vibrio harveyi, bakteri patogen yang menyebabkan penyakit vibriosis pada udang. Percobaan kedua dilakukan untuk mengevaluasi pengaruh immonustimulasi Trichoderma sp. terhadap imunitas udang serta pengaruh protektif terhadap V. harveyi. Sekelompok udang disuntik dengan konsentrasi hambatan minimum (minimum inhibitory concentration, MIC) yang diperoleh dari hasil percobaan pertama, dan seminggu kemudian udang diuji tantang dengan V. harveyi (profilaksis). Kelompok udang lain diuji tantang dengan V. harveyi sebelumnya untuk kemudian disuntik dengan Trichoderma sp. (therapeutic). Kontrol positif, yang hanya diuji tantang dengan V. harveyi, dan kontrol negatif, yang tidak mendapat baik Trichoderma sp. maupun V. harveyi. Hasil percobaan pertama menunjukkan bahwa 600 ppm merupakan konsentrasi MIC Trichoderma sp. yang memberikan efek penghambatan maksimal terhadap V. harveyi. Sedangkan hasil percobaan kedua, kelompok udang yang mendapatkan Trichoderma sp. baik sebagai profilaksis maupun therapeutic menunjukkan bahwa Trichoderma sp. memberikan efek perlindungan terhadap infeksi V. harveyi secara signifikan lebih tinggi daripada kontrol positif dan lebih rendah daripada kontrol negatif. Total hemocyte count (THC) dan differential hemocyte (DHC), indeks fagositik dan aktivitas fenoloksidase kelompok perlakuan profilaksis atau perlakuan therapeutic berbeda baik dengan kontrol positif maupun negatif. Untuk itu dapat disimpulkan bahwa Trichoderma sp. dapat digunakan dalam tindakan pencegahan dan pengobatan infeksi V. harveyi pada udang putih. Kata kunci: Trichoderma sp., V. harveyi, immunostimulan